Comparison of agility in 13-16-year-old volleyball and football players and non-athletes - Stamm, R.; Stamm, K.; Stamm, M. (Papers on Anthropology, 2022)
The aim of the study was to find and compare the agility abilities and anthropometric characteristics of 13-16-year-old volleyball and football players and adolescents not engaged in sports. The following research questions were posed: to find the agility results and anthropometric characteristics of volleyball and football players and non-athletes and to compare the agility results and anthropometric characteristics between athletes and not non-athletes and between different sports in both boys and girls. In total, 63 subjects participated in the study - 45 of them practised sports and 18 did not. Among those who practised sports, there were 19 volleyball and 26 football players. The following agility tests were applied in the study: T-test, four corners test, 5-0-5 run test and Illinois test. For data analysis, the Microsoft Excel program was used. The subjects` height, weight, fat percentage and fat amount were measured. The means, minimum and maximum values, standard deviations, and body mass indices were calculated. To find correlations within the groups, correlation analysis was used. To establish statistical significance between the groups, Student`s t-test was used. The results revealed that, among both boys and girls, athletes were statistically significantly faster than non-athletes; only in Illinois test, there was no statistically significant difference. In girls, there were statistically significant differences between athletes and non-athletes in weight, fat percentage, fat amount and body mass index. In boys, however, there were no statistically significant differences in the body build characteristics between athletes and non-athletes. Football players were better in agility tests compared to volleyball players. Football boys were statistically significantly taller and older, and, in most tests, they were also statistically significantly faster than volleyball boys. Volleyball girls were statistically significantly taller and weighed more, but, in all tests, football girls were statistically significantly faster than volleyball girls. In all groups, the fat-related indicators, like fat percentage, fat amount and body mass index, were in mutual correlation. According to the body mass index scale, 45 subjects were of normal weight, 6 were overweight, 1 was obese and 11 were underweight. The authors of the paper hold the view that, namely in this age group, the athletes of sports games should practice agility and be tested in it, as, according to literature, the development of agility slows down at the age of 16-17 years, and therefore, can be one of the obstacles for reaching the top in adult athletes.